1988
DOI: 10.2118/88-06-08
|View full text |Cite
|
Sign up to set email alerts
|

The Physical Chemistry Of The Hot Water Process

Abstract: The roles in the hot waterprocess ofsodium hydroxide, surfac-tants, watersolubleelectrolytesfinesolidsandelectricproper-ties of the bitumenlwater and solidslwater interfaces are examined. Recovery of bitumen from low-to medium-grade oil sands can be increased by ensuring the fine solids remain dis-persed during digestion by adjustment of digestion water salin-ity and pH. Recovery of bitumen from high-grade oil sands appears to be controlled by surfactants which affect bitumen-water interfacial tension and the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
24
0

Year Published

1997
1997
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(26 citation statements)
references
References 0 publications
2
24
0
Order By: Relevance
“…In other cases, bitumen recovery was not affected up to 150 mM (3450 ppm) of sodium ion addition (in the form of NaHCO 3 ). Although adding NaHCO 3 would increase the slurry pH, a similar function to adding NaOH, this level of sodium addition was much higher than that in the transition/coagulated region (50-75 mM) even in the presence of 0.048 wt.% NaOH (of oil sands) (Takamura and Wallace, 1988).…”
Section: Mono-valent Metal Ions (Na K)mentioning
confidence: 95%
See 2 more Smart Citations
“…In other cases, bitumen recovery was not affected up to 150 mM (3450 ppm) of sodium ion addition (in the form of NaHCO 3 ). Although adding NaHCO 3 would increase the slurry pH, a similar function to adding NaOH, this level of sodium addition was much higher than that in the transition/coagulated region (50-75 mM) even in the presence of 0.048 wt.% NaOH (of oil sands) (Takamura and Wallace, 1988).…”
Section: Mono-valent Metal Ions (Na K)mentioning
confidence: 95%
“…Takamura and Chow (1983) ;Takamura, (1985); Takamura and Wallace, (1988) used the micro-disintegration experiment to examine the development and movement of the bitumen/water/sand three-phase contact line on an individual sand grain over a period of time.…”
Section: Bitumen Liberation Lump Size Reduction and Bitumen Liberatiomentioning
confidence: 99%
See 1 more Smart Citation
“…Clark et al (1932) and Clark (1 949) showed that the bitumen recovery was poor under acidic conditions, but was greatly improved for pH above 7. Takamura et al (1983Takamura et al ( , 1988) have shown through a crumbling test that at a pH of 11.8, the bitumen recovery from oil sand is highest. The reason for high bitumen recovery in an alkaline aqueous solution was explained on the basis of disjoining pressure of water between the sand and bitumen.…”
mentioning
confidence: 99%
“…However, for poor processing ores, many technical challenges exist to achieve a satisfactory bitumen recovery and froth quality. The significant impact of chemical species and fine clays present in the slurry on oil sands ore processability has been recognized both in industrial operations and in laboratory tests (Sandford and Seyer, 1979;Sanford, 1983;Takamura and Wallace, 1988;Smith and Scharmm, 1992;Zhou et al, 1999). The difference in the processability between good and poor processing ores is of great socioeconomic importance.…”
mentioning
confidence: 99%